2021
DOI: 10.3389/fpubh.2021.712481
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personal Cooling on Performance, Comfort and Heat Strain of Healthcare Workers in PPE, a Study From West Africa

Abstract: Background: Personal protective equipment (PPE) is an essential component of safely treating suspected or confirmed SARS-CoV-2 patients. PPE acts as a barrier to heat loss, therefore increasing the risk of thermal strain which may impact on cognitive function. Healthcare workers (HCWs) need to be able to prioritize and execute complex tasks effectively to ensure patient safety. This study evaluated pre-cooling and per-cooling methods on thermal strain, thermal comfort and cognitive function during simulated em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
5
3
0
Order By: Relevance
“…Prolonged physical exertion and fatigue in physically demanding environments can potentially lead to occupational injuries,22 although at temperatures considerably exceeding those experienced by surgeons. Improved thermal comfort with a cooling vest is consistent with studies conducted in real time2 23 and simulation24 and extends previous work by evaluating surgeons in a clinical environment.…”
Section: Discussionsupporting
confidence: 84%
“…Prolonged physical exertion and fatigue in physically demanding environments can potentially lead to occupational injuries,22 although at temperatures considerably exceeding those experienced by surgeons. Improved thermal comfort with a cooling vest is consistent with studies conducted in real time2 23 and simulation24 and extends previous work by evaluating surgeons in a clinical environment.…”
Section: Discussionsupporting
confidence: 84%
“…Zhu et al (4), conducted a survey of clinical research staff across China to assess perceptions on how procedural changes resulting from the COVID-19 pandemic impacted four core areas: subject enrollment, patient care, study supplies and data management, and research milestones and quality management. The results of the survey support findings from several other studies (5)(6)(7)(8)(9)(10)(11); yet, decentralized clinical trials are becoming more prevalent post-pandemic.…”
Section: Introductionsupporting
confidence: 84%
“…Our study showed that over 2,000 research members from study sites covering the east to the west of China accepted the nationwide survey, and the results exhibited a generally negative attitude toward the impact of the COVID-19 pandemic on the conduct of clinical trials, especially regarding subject recruitment and patient care. Consistent with several studies from some other countries (22)(23)(24)(25)(26)(27), the negative impact of the pandemic includes aspects such as inevitable delays in follow-up visits, challenges in handling…”
Section: Discussionsupporting
confidence: 68%